Improving Primary Teacher Education Students' Writing Performance Using Flipped Classroom - Nurul Masyithah Rery; Niamika El Khoiri (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study aimed to improve students' writing performance in ESP subject by implementing Flipped Classroom and Collaborative activities. Classroom action research was applied as the method in this study was. According to the data obtained, 88,89% of the students experienced improvement at least 10 points compared to their initial writing product. Students active participation also improved which was shown by the average score that was above 3,0 points obtained from peer assessment rubric. Therefore, the combination of these two strategies was proven successful in improving students' writing performance in ESP subject. Abstrak: Penelitian ini bertujuan untuk meningkatkan kinerja menulis bahasa Inggris siswa sebagai mata pelajaran ESP dengan menerapkan kegiatan Flipped Classroom dan Collaborative. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan kelas. Menurut data yang diperoleh, 88,89% dari siswa mengalami peningkatan setidaknya 10 poin dibandingkan dengan produk penulisan awal mereka. Partisipasi aktif siswa juga mengalami peningkatan yang ditunjukkan oleh skor rata-rata di atas 3,0 poin yang diperoleh dari rubrik penilaian sejawat. Dengan demikian, kombinasi dari dua strategi tersebut terbukti berhasil meningkatkan kinerja menulis bahasa Inggris siswa sebagai mata pelajaran ESP.